Upscaling of Permanent Magnet Dismantling and Recycling through VALOMAG Project - Fernando Coelho; Shoshan Abrahami; Yongxiang Yang; Benjamin Sprecher; Zhijie Li; Nour-Eddine Menad; Kathy Bru; Thibaut Marcon; Cyril Rado; Boris Saje; Marie-Lise Sablayrolles; Virginie Decottignies (Materials Proceedings, 2021)
Neodymium-Iron-Boron (NdFeB) based permanent magnets are indispensable in today’s technology-driven society. Moreover, their use is likely to increase since they are key in clean energy applications such as wind turbines, hybrid/electric vehicles, and electric bikes. They contain critical raw materials as rare earth elements are used. Indeed, permanent magnets are considered strategic materials by the EU, and their recycling represents a potential secondary supply to decrease the import dependence. The VALOMAG project is developing a technical solution to recover rare earth (RE) based permanent magnets by dismantling end-of-life (EoL) products such as computer hard disc drives, electric motors, and generators from electric vehicles and wind turbines. It also assesses two short loop recycling technologies: Hydrogen Decrepitation (HD) or Hydrogenation–Disproportionation–Desorption–Recombination (HDDR) and strip-casting for high and medium quality magnet wastes; and hydrometallurgical processes for EoL low-quality magnets. Moreover, Life Cycle Assessment (LCA) and Process Integration with a Flowsheet simulation tool will integrate the whole recycling value chain (collection, dismantling, physical and chemical treatment options, and re-manufacturing) and assess the environmental impact and processes efficiency. A market study on the types and expected future quantities for the scrap magnets and the characterisation of the EoL magnets from hard disc drives (HDD) will be presented as preliminary results. Pre-treatment and sorting of 2.5 tons of NdFeB magnets scraps were carried out, and the two short loop recycling routes and the hydrometallurgical route are under investigation at the lab and pilot scale. The results will be used to develop a process integration and to assess the three routes through LCA.